2006
DOI: 10.1055/s-2005-858720
|View full text |Cite
|
Sign up to set email alerts
|

Katarakt-Operation bei Patienten mit Glaucoma fere absolutum

Abstract: Patients with progressive cataract and end-stage glaucoma can benefit from cataract surgery. Although marked visual field defects were present, an increase in visual acuity as well as a decrease of intraocular pressure may be achieved without worsening of the visual fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The results of our study, which showed a significantly improved BCVA without worsening of the VF after PHACO IOL, are similar to those previously reported (1,3,6). The IOP and the number of antiglaucoma medications after PHACO IOL in our study were stable.…”
Section: ; 6 (1): 65-73supporting
confidence: 91%
See 4 more Smart Citations
“…The results of our study, which showed a significantly improved BCVA without worsening of the VF after PHACO IOL, are similar to those previously reported (1,3,6). The IOP and the number of antiglaucoma medications after PHACO IOL in our study were stable.…”
Section: ; 6 (1): 65-73supporting
confidence: 91%
“…That is why surgeons may be hesitant about recommending PHACO IOL for patients with end-stage glaucoma, because of concerns regarding the possibility of the occurrence of the "wipe-out" phenomenon and the questionable improvement of functional vision. Therefore, only few reports are available dealing with the outcome of PHACO IOL in eyes with endstage glaucoma (1,3,6).…”
Section: ; 6 (1): 65-73mentioning
confidence: 99%
See 3 more Smart Citations